Neuroprotective Effect of Optogenetics Varies With Distance From Channelrhodopsin-2 Expression in an Amyloid-β-Injected Mouse Model of Alzheimer’s Disease - Cui, Xiaorui; Zhang, Feng; Zhang, Hui; Huang, Xi; Wang, Kewei; Huang, Ting; Yang, Xifei; Zou, Liangyu (Frontiers in Neuroscience, 2020)
Background: Alzheimer’s disease (AD) is a progressive neurodegenerative disease that is the most common cause of dementia. Optogenetics uses a combination of genetic engineering and light to activate or inhibit specific neurons in the brain. Objective: To examine the effect of activation of glutamatergic neurons in the hippocampus of mice injected with Aβ1-42 on memory function and biomarkers of neuroinflammation and neuroprotection in the brain to elucidate the clinical utility of optogenetic neuro-modulation in AD. Methods: AAV5-CaMKⅡ-CHR2-mCherry (Aβ-CHR2 mice) or AAV5-CaMKⅡ-mCherry (Aβ-non-CHR2 mice) was injected into the dentate gyrus (DG) of the bilateral hippocampus of an Aβ1-42-injected mouse model of AD. The novel object recognition test was used to investigate working memory (M1), short-term memory (M2), and long-term memory (M3) after Aβ1-42 injection. Hippocampus tissues were collected for immunohistochemical analysis. Results: Compared to controls, M1 and M2 were significantly higher in Aβ-CHR2 mice, but there was no significant difference in M3; NeuN and synapsin expression were significantly increased in the DG of Aβ-CHR2 mice, but not in CA1, CA3, the SVZ or the ENT; GluR2 and IL-10 expression were significantly increased and GFAP expression was significantly decreased in CA1, CA3, the DG, and the SVZ of Aβ-CHR2 mice, but not in the ENT. Conclusion: Activation of glutamatergic neurons by optogenetics in the bilateral DG of an Aβ-injected mouse model of AD improved M1 and M2, but not M3. A single-target optogenetics strategy has spatial limitations; therefore a multiple targeted optogenetics approach to AD therapy should be explored.